P2.27 High satisfaction with and loyalty to getcheckedonline.com among first-time users of an online sti testing service in british columbia, canada. (8th July 2017) - Gilbert, Mark; Thomson, Kimberly; Salway, Travis; Haag, Devon; Grennan, Troy; Buchner, Chris; Tyndall, Mark; Krajden, Mel; Ogilvie, Gina; Shoveller, Jean
Abstract : Introduction: Positive user experiences are key to trust and repeated use of online services (known as e-Loyalty). GetCheckedOnline (GCO) is an online testing service for HIV/STI where clients complete a risk assessment, print lab forms, submit specimens at a lab, and retrieve results online (if negative) or by phone. We surveyed GCO clients on their perceptions of using the service. Methods: We invited first-time GCO users (who consented to be contacted for research) to complete an anonymous online survey 2 weeks following reporting of test results. Survey questions were analysed descriptively and included demographics, reason for test, and how participants heard about GCO. Satisfaction, convenience, ease of use, and e-Loyalty (intention to use again, recommend to others) were measured using 5-point Likert scales and collapsed (low to neutral vs high responses). Results: Between July 2015-Sept 2016, 23% of 1099 first-time GCO users consented to be contacted for research and 136/208 (65%) of users contacted agreed to participate in the survey. Participants had a median age of 33 years, 80% were white, 67% male, 43% straight, and 43% men who have sex with men. The most common testing reasons were: routine test (64%), risk event/exposure (44%) and new relationship (22%). Participants heard about GCO from clinics/health providers (38%), campaigns (26%), social media (18%), and friends or partners (13%). Almost all participants were satisfied with GCO overall (93%) and with their experience of receiving results (96%), 92% agreed GCO was convenient, 87% found GCO easy to use, and 83% rated the experience of submitting specimens as good or excellent. E-Loyalty was also high: 97% intended to use GCO again and 96% would recommend GCO to others. Conclusion: We found very high satisfaction with and loyalty to GCO among first-time users, indicating a successful service model from a client perspective. In addition to uptake and test outcomes, user experience is a key outcome for evaluation of online HIV/STI testing services.